Preparation method and application of PbO-Bi2O3-SiO2-CuO coated gold powder and gold conductor paste
Preparation of PbO-Bi2O3-SiO2-CuO glass-covered gold powder by sol-gel method solves the problem of poor adhesion when mixing traditional glass powder with gold powder, realizes uniform distribution and high adhesion between the gold powder and the substrate, and improves the Conductivity and solder resistance simplify the process and reduce costs.
Patent Information
- Application Number
- CN202411341653.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-25
- Publication Date
- 2025-01-03
AI Technical Summary
When traditional glass powder is mixed with gold powder, the surface of the gold powder cannot be fully wetted and spread, resulting in poor adhesion and affecting electrical conductivity. The uneven distribution of the glass leads to discontinuous conductive paths, making it difficult to form a firm bond with the substrate.
The sol-gel method is used to prepare PbO-Bi2O3-SiO2-CuO glass-covered gold powder to form a core-shell structure. During the low-temperature sintering process, the glass melts into a liquid phase, and evenly contacts the gold powder and the substrate to enhance binding force.
The uniform distribution and high adhesion between the gold powder and the substrate are achieved, the conductive path discontinuity is avoided, the conductive performance and welding resistance of the gold electrode after sintering are improved, and the preparation cost and process complexity are reduced.
Smart Images

Figure CN119252524A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of electronic materials and relates to a method for preparing a core-shell structure powder by a sol-gel method using glass-coated gold powder and its application. 2 O 3 -SiO 2 -CuO glass coated gold powder and its preparation method and application. Background Art
[0002] Conductive gold paste plays a vital role in flexible electronics, microelectronics, optoelectronic devices, especially in high-tech fields such as military, aerospace, and precision testing instruments due to its excellent conductivity and stability. Gold powder and glass are two key raw materials used in conductive gold paste. Gold powder provides excellent conductivity and has excellent oxidation resistance, but it is difficult for gold electronic paste to generate bonding with the substrate when used. The characteristic of gold not being easily oxidized is conducive to forming adhesion with metals, but not conducive to forming adhesion with glass or ceramics. Therefore, it is necessary to add glass powder as a bonding phase to provide bonding, and at the same time, the glass powder is transformed into a liquid phase at high temperature, which plays a role in promoting the dense sintering of gold particles. However, there is also a non-wetting situation between glass and gold powder, which leads to the non-dense sintering of gold paste and the inability to achieve the effect of bonding the gold conductor and the substrate.
[0003] The above problems are usually improved by introducing inorganic additives or changing the glass formula to achieve the effect of wetting with gold particles. For example, V is added in patent JPH0799011A. 2 O 5 , increase V 2 O 5 The content of lead-free microcrystalline glass SiO can improve the bonding strength between the metal layer and the substrate, thereby improving the overall performance of the circuit substrate; Patent CN101436441A adds lead-free microcrystalline glass SiO 2 -Al 2 O 3 -BaO-B 2 O 3 -Bi 2 O 3 -Na 2 O series glass-ceramic powder or SiO 2 -Al 2 O 3 -BaO-B 2 O 3 -Bi 2 O 3 -Na 2 OK 2O-based microcrystalline glass powder changes the microstructure of the gold electrode paste, thereby improving the paste's conductivity, printing performance and connection reliability; PbO-SiO 2 -Al 2 O 3 -ZnO glass, and add molybdenum to the glass, which can form a strong chemical bond with silicon, thereby enhancing the bonding force between the gold electrode and the silicon wafer; Patent CN108053915A adds copper-containing organic matter to zinc borosilicate glass and barium borosilicate glass, which improves the bonding ability of the gold paste with the alumina substrate after sintering; Patent CN4974560A mixes the substrate LTCC powder material and LTCF powder material, in which the LTCC substrate material is Li 2 Mg 0.3 Zn 0.7 SiO 4 and Zn 0.8 Mg 0.2 TiO 3 Ceramics and CaO-B 2 O 3 -ZnO-SiO 2 、ZnO-B 2 O 3 -SiO 2 glass, and LTCF powder material is made of (Ni 0.5-x Cu x Zn 0.5 )(Fe 2 O 3 ) 0.98 ZnO-B 2 O 3 -SiO 2 Made of glass, it can adjust the sintering shrinkage rate of gold inner electrode conductor paste and obtain gold inner electrode paste with high bonding strength with LTCC and LTCF; Patent CN114464339A uses lead-free glass formula CaO-B 2 O 3 -SiO 2 -ZnO-CuO-Bi 2 O 3 -MnO-Fe 2 O 3 The sintered gold paste has good adhesion to the substrate after testing.
[0004] In order to achieve better wetting and fluxing effects, the particle size of glass powder is usually required to be similar to that of gold powder. However, traditional glass needs to be melted at high temperature, which consumes a lot of energy. It is difficult to obtain glass powder that matches the particle size of gold powder through traditional ball milling and mechanical mixing. As a result, when glass powder and gold powder are mixed and sintered, the surface of gold powder cannot be fully wetted and spread, resulting in poor adhesion, and the gold electrode and substrate are not firmly bonded. In addition, the unevenly distributed glass has local agglomeration, resulting in discontinuity of the conductive path, thereby affecting the conductivity of the gold electrode after sintering.
[0005] Therefore, it is necessary to provide a method for preparing a gold paste that has low energy consumption, more uniform distribution of gold powder and higher adhesion to the substrate. Summary of the invention
[0006] The purpose of the present invention is to solve the problems existing in the prior art and provide a method and application of preparing gold paste with low energy consumption, more uniform distribution of gold powder and higher adhesion to the substrate. Compared with the traditional mixing of glass frit and gold powder, the sol-gel method is adopted to coat the glass with the surface of the gold powder, which improves the mixing uniformity of the gold powder and the glass powder, and the glass has better wettability with the gold powder and better bonding with the substrate.
[0007] To achieve the above object, the technical solution adopted by the present invention is as follows:
[0008] A low-temperature sintered anti-oxidation gold powder, comprising gold powder and a coating layer on the surface of the gold powder; the coating layer is PbO-Bi 2 O 3 -SiO 2 -CuO glass composition.
[0009] The method for preparing the coating layer of the gold powder of the present invention adopts a sol-gel method to obtain a powder with a core-shell structure, so that the contact between the glass melted into a liquid phase and the gold powder body during the sintering process is more uniform, and at the same time, the glass coating layer as a bonding phase strengthens the bonding between the gold electrode and the substrate, and the further prepared gold paste has excellent bonding strength with the substrate.
[0010] The present invention also provides a method for preparing the low-temperature sintered anti-oxidation gold powder as described above, comprising the following steps:
[0011] (1) Use organic and inorganic precursors to dissolve in a certain solvent to obtain transparent PbO-Bi 2 O 3 -SiO 2 -CuO glass sol.
[0012] (2) Disperse gold powder with a particle size of 0.5 to 2 microns in water or ethanol, and add the above-mentioned PbO-Bi 2 O 3 -SiO 2-CuO glass sol, gold quality is PbO-Bi 2 O 3 -SiO 2 -CuO glass sol contains 7-49 times the mass of glass. Stir and heat continuously in air atmosphere to remove solvent and obtain PbO-Bi 2 O 3 -SiO 2 -CuO glass coated gold powder.
[0013] (3) The PbO-Bi 2 O 3 -SiO 2 -CuO glass coated gold powder is calcined at 200-500℃ for 2-4 hours to remove the residual solvent and precursor decomposition products in the gel and make PbO-Bi 2 O 3 -SiO 2 -CuO glass gel is completely densified to form a glassy substance. After cooling, PbO-Bi 2 O 3 -SiO 2 -CuO glass coated with gold powder, in which PbO-Bi 2 O 3 -SiO 2 -CuO glass quality is PbO-Bi after calcination 2 O 3 -SiO 2 -CuO glass coated gold accounts for 2-12% by mass.
[0014] (4) The specific steps include: 2 O 3 -SiO 2 -CuO glass coated with gold powder and organic binder mixed, where PbO-Bi 2 O 3 -SiO 2 -The mass ratio of the CuO glass-coated gold powder is 80% to 97%, and the mass ratio of the organic binder is 3% to 20%.
[0015] (5) The prepared gold paste can be coated on a substrate with a thickness of 20-150 microns, heated to 400-600°C in an air atmosphere, kept at a constant temperature for 1-2 hours, and then heated to 650-850°C for calcination for 1-4 hours to obtain a gold electrode. The substrate includes ceramics, glass, silicon, etc. The square resistance of the prepared gold electrode can be measured using a four-probe resistance meter.
[0016] Principle of the invention:
[0017] The gold powder prepared by the present invention has low energy consumption, more uniform distribution of gold powder and higher adhesion with the substrate. The gold powder is a powder with a core-shell structure, and its coating layer is composed of PbO-Bi 2 O 3 -SiO 2 -CuO glass composition. Prepared by sol-gel method and heat treated to form a dense coating.
[0018] Among them, the glass coating layer can soften and form a liquid phase during the sintering process, wetting the gold powder and the substrate, so that the sintered gold film and the alumina substrate have good bonding strength.
[0019] In the glass-coated gold powder of the present invention, copper oxide is added to the lead-bismuth-silicon glass system in order to increase the wetting of the glass and the substrate and enhance the adhesion between the glass and the substrate.
[0020] The gold paste prepared in the present invention can be co-fired with the substrate to form a dense conductive pattern and generate a strong bonding force with the substrate. After sintering, the gold electrode has a uniform and moderate internal stress distribution, a small square resistance, and strong solder resistance. The pass rate of reliability tests such as heating aging and accelerated life is high.
[0021] Beneficial effects:
[0022] The glass-coated gold powder prepared by the present invention is a powder with a core-shell structure, and its coating layer is composed of PbO-Bi 2 O 3 -SiO 2 -CuO glass. The coating layer can improve the uniformity of the distribution of glass and gold powder and produce a strong adhesion with the substrate.
[0023] The glass coating can improve the uneven distribution of gold powder and glass, and can effectively avoid the discontinuity of the conductive path caused by glass agglomeration, which leads to the degradation of device performance. In addition, after the glass melts into a liquid phase during the sintering process, the contact with the gold powder is more uniform, which promotes the sintering of the gold powder. The addition of copper oxide to the glass system not only promotes the wetting of glass and gold particles, but also enhances the wetting of glass and substrate, and enhances the bonding between the gold electrode and substrate.
[0024] The preparation cost of the invention is low and the process is simple. BRIEF DESCRIPTION OF THE DRAWINGS
[0025] Figure 1 7.5% mass ratio PbO-Bi 2 O 3 -SiO 2 -Scanning electron microscope image of CuO glass coated with 92.5% gold powder by mass;
[0026] Figure 2 2.5% mass ratio PbO-Bi 2 O3 -SiO 2 - Scanning electron microscope image of the gold electrode obtained after sintering at 850°C with 97.5% by mass gold paste coated with CuO glass;
[0027] Figure 3 5% mass ratio PbO-Bi 2 O 3 -SiO 2 - Scanning electron microscope image of the gold electrode obtained after sintering at 850°C with 95% by mass gold paste coated with CuO glass;
[0028] Figure 4 7.5% mass ratio PbO-Bi 2 O 3 -SiO 2 - Scanning electron microscope image of the gold electrode obtained after sintering at 850°C with 92.5% by mass gold paste coated with CuO glass;
[0029] Figure 5 7.5% mass ratio PbO-Bi 2 O 3 -SiO 2 Scanning electron microscope image of the gold electrode obtained after sintering at 850℃ with 92.5% mass ratio of -CuO glass added to gold paste. DETAILED DESCRIPTION
[0030] The present invention will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are only used to illustrate the present invention and are not intended to limit the scope of the present invention. In addition, it should be understood that after reading the content taught by the present invention, those skilled in the art can make various changes or modifications to the present invention, and these equivalent forms fall within the scope limited by the appended claims of the application equally.
[0031] Average square resistance: Use ST2258C digital four-probe to test the square resistance of the copper film on the sintered alumina substrate. Adjust the four-probe measurement mode to the square resistance mode, place the sintered alumina substrate on the test bench, make the probe face the center of the copper film surface and slowly press down, after the copper film is completely pressed, close the loop and get the square resistance value. Test and calculate the average square resistance of 5 samples (i.e. alumina substrates) under the same preparation conditions.
[0032] Example 1
[0033] As a preferred technical solution, a PbO-Bi 2 O 3 -SiO 2 -Method for preparing CuO glass coated gold powder and gold paste, the specific steps are as follows:
[0034] Use 2g of ethyl orthosilicate, add it to deionized water, heat and hydrolyze at 70℃ until transparent and clear to obtain solution A. Take 2.5g of bismuth nitrate, 1.5g of lead nitrate, and 1.5g of copper sulfate pentahydrate, heat and stir at 70℃ until clear to obtain solution B. Mix the two precursor solutions evenly, continue stirring at 70℃ for 6 hours, and obtain transparent and clear PbO-Bi 2 O 3 -SiO 2 -CuO glass sol. 50g gold powder with a particle size of 0.5-2 microns was ultrasonically dispersed in ethanol, and then added dropwise to 3.75g PbO-Bi 2 O 3 -SiO 2 -CuO glass sol was stirred continuously in air atmosphere and heated at 70°C to remove the solvent to obtain PbO-Bi 2 O 3 -SiO 2 -CuO glass coated nano-gold powder. The gel coated gold powder was calcined at 300℃ for 1h in air atmosphere to obtain PbO-Bi 2 O 3 -SiO 2 -CuO glass coated nano-gold powder ( Figure 1 ).
[0035] The obtained PbO-Bi 2 O 3 -SiO 2 -CuO glass-coated nano-gold powder was taken 8g, weighed with 1g of diethylene glycol butyl ether, 0.5g of diethylene glycol butyl ether acetate, 0.4g of ethyl cellulose and 0.1g of dispersant, mixed evenly with a three-roll mill, and then the gold paste was evenly coated on the surface of the alumina ceramic sheet with a 75-micron scraper. The temperature was raised to 400-600°C in an air atmosphere, kept at a constant temperature for 1-2h, and then raised to 850°C and calcined for 1-4 hours to obtain a ceramic sheet and a gold electrode structure ( Figure 2 ).
[0036] The square resistance of the gold electrode measured by a four-probe resistance meter was 2.53 mΩ / □.
[0037] Example 2
[0038] This embodiment provides a PbO-Bi 2 O 3 -SiO 2 -CuO glass coated micron gold powder and its gold paste preparation method.
[0039] The specific preparation method is the same as that of Example 1, except that the mass of the glass sol in Example 1 is increased to 4 g. The obtained ceramic sheet and gold electrode structure ( Figure 3 ).
[0040] The square resistance of the gold electrode measured by a four-probe resistance meter was 2.25 mΩ / □.
[0041] Example 3
[0042] This embodiment provides a PbO-Bi 2 O 3 -SiO 2 -CuO glass coated micron gold powder and its gold paste preparation method.
[0043] The specific preparation method is the same as that of Example 1, except that the mass of the glass sol in Example 1 is increased to 4.25 g. The obtained ceramic sheet and gold electrode structure ( Figure 4 ).
[0044] The square resistance of the gold electrode measured by a four-probe resistance meter was 2.1 mΩ / □.
[0045] Example 4
[0046] This embodiment provides a PbO-Bi 2 O 3 -SiO 2 -CuO glass coated micron gold powder and its gold paste preparation method.
[0047] The specific preparation method is the same as that of Example 1, except that the second step sintering temperature in Example 1 is reduced to 800°C. The obtained ceramic sheet and gold electrode structure ( Figure 5 ).
[0048] The square resistance of the gold electrode measured by a four-probe resistance meter was 2.49 mΩ / □.
[0049] Comparative Example 1
[0050] Take 8g of nano gold powder and weigh 7.5wt% of the gold powder. 2 O 3 -SiO 2 -CuO glass powder is weighed and mixed with 1g of diethylene glycol butyl ether, 0.5g of diethylene glycol butyl ether acetate, 0.4g of ethyl cellulose and 0.1g of dispersant, and then the gold paste is evenly coated on the surface of the ceramic sheet with a 75-micron scraper. The temperature is raised to 400-600°C in an air atmosphere, kept at a constant temperature for 1-2 hours, and then raised to 850°C and calcined for 1-4 hours to obtain a ceramic sheet and a gold electrode structure.
[0051] The square resistance of the gold electrode measured by a four-probe resistance meter was 2.49 mΩ / □.
[0052] The conductivity and adhesion of the glass-coated gold paste / alumina substrate prepared in the above embodiment were tested, and the specific values are shown in Table 1. Table 1 Square resistance of gold electrodes of Examples 1-5
Claims
1. A glass-coated gold powder, characterized in that: It includes gold powder and a coating layer located on the surface of the gold powder; the coating layer is composed of PbO-Bi2O3-SiO2-CuO glass.
2. A glass-coated gold powder as claimed in claim 1, characterized in that The content of the coating layer is 1-10wt%; the thickness of the coating layer is below 10nm, the coating layer is composed of PbO-Bi2O3-SiO2-CuO glass, and the content of each component is as follows in molar percentage: 10-20.0% PbO, 20-30.0% SiO2, 30-50.0% Bi2O3, 0-5.0% CuO.
3. A glass-coated gold powder as claimed in claim 1 or 2, characterized in that The preparation method comprises the following steps: 1) Using a sol-gel method, a silicon-containing precursor is added to a mixed solution of water and ethanol for hydrolysis, and after the hydrolysis is complete, an inorganic bismuth salt, an inorganic lead salt, and an inorganic copper salt are added; the mixture is stirred and dissolved at 50 to 70° C. until transparent, and then the stirring is continued for 1 to 3 hours to obtain a PbO-Bi2O3-SiO2-CuO glass sol solution. 2) Ultrasonic dispersion of gold powder with a particle size of 0.5 to 2 microns in ethanol or water, then drop a certain amount of PbO-Bi2O3-SiO2-CuO glass sol solution, continuously stir and heat to remove the solvent, and obtain PbO-Bi2O3-SiO2-CuO glass-coated gold powder; 3) After calcining at 300-500°C for 0.5-1 hour, PbO-Bi2O3-SiO2-CuO glass-coated gold powder is obtained after cooling.
4. The use of a PbO-Bi2O3-SiO2-CuO glass-coated gold powder as claimed in claim 1 or 2, characterized in that: Conductive paste for electronic packaging was prepared using PbO-Bi2O3-SiO2-CuO glass coated gold powder as a conductive agent.
5. A gold paste prepared by coating gold powder with PbO-Bi2O3-SiO2-CuO glass as claimed in claims 1 to 5, characterized in that The mass percentage of each component is: The organic polymer is one or more of polyacrylate, ethyl cellulose, polyvinyl alcohol, and polyvinyl butyral ester, and the organic solvent is one or more of pineol, diethylene glycol butyl ether, diethylene glycol butyl ether acetate, and dodecyl alcohol ester.
6. The use according to claim 5, characterized in that: The conductive paste for electronic packaging is also printed on the surface of the substrate, and then dried and co-fired in sequence to obtain.
7. A method for preparing a gold electrode, characterized in that The gold paste is printed onto the alumina substrate by screen printing, the temperature is raised to 400-600°C in an air atmosphere, the temperature is kept constant for 1-2 hours, and then the temperature is raised to 750-900°C and calcined for 10-90 minutes to obtain a gold electrode, which can be used in the field of electronic materials.
8. A gold electrode as claimed in claim 8, characterized in that Compared with gold electrodes with glass added in other forms, the sheet resistance is 2 to 6 mΩ / □ and the adhesion to the substrate is 15 to 21N.
Citation Information
Patent Citations
Thick film nanometer gold electrode slurry and preparation method thereof
CN101436441A
Gold-based conductive paste for silk-screen printing and preparation method of gold-based conductive paste
CN108053915A
Molybdenum-containing glass frit for electroconductive paste composition
US20150243810A1